The Manatee Scientist : Saving Vulnerable Species - Lourie, Peter (Boston : Houghton Mifflin Books for Children, 2011)
Scientists in Florida, West Africa, and the Amazon Basin share information with the goal of protecting the docile and sometimes elusive manatee.
Includes bibliographical references (p. 72) and index.
Keywords: Manatees -- Juvenile literature. -- Conservation; Marine mammalogists -- Juvenile literature; Manatees -- Conservation; Marine mammalogists